Growth of Trypanosoma cruzi in a cloned macrophage cell line and in a variant defective in oxygen metabolism. - Tanaka, Y (1983)
A continuous cloned murine macrophage-like cell line, clone 16 derived from J774, has been found upon appropriate stimulation to be capable of oxidizing glucose by the hexose monophosphate shunt and producing O2- and H2O2. A variant in oxidative metabolism, clone C3C, was selected from this cell line which under similar conditions is unable to produce significant amounts of O2- and H2O2. When cells of the parental clone 16 were infected with epimastigotes of Trypanosoma cruzi, there was significant killing or growth inhibition of the parasites at 3 to 4 days after infection. In contrast, the parasites grew in the oxidative variant, clone C3C. Trypomastigote forms of T. cruzi were found to be only partially killed in the parental clone 16 but grew abundantly in the oxidative variant. Infection of the parental clone, but not the variant, was sufficient to stimulate oxygen metabolism as demonstrated by the increased reduction of nitro blue tetrazolium. Studies on the killing of T. cruzi epimastigotes in cell-free suspension by xanthine-xanthine oxidase indicated that 90% of the killing was catalase sensitive and due to H2O2, with at most 7 to 8% killing which could be inhibited by scavengers of . OH and singlet oxygen (1O2). In the in vitro experiment with H2O2 produced by glucose and glucose oxidase, the 50% lethal doses of epimastigotes and trypomastigotes were 6.0 and 8.7 nmol of H2O2 per min per ml, respectively, indicating that trypomastigotes were more resistant to killing by H2O2 than epimastigotes were. A reconstitution experiment of trypanocidal activity in clone C3C by ingestion of zymosan particles coupled with glucose oxidase showed that H2O2 was essential for this cytocidal process in the macrophage cell line. These results provide clear evidence for killing of an intracellular parasite by a continuous macrophage-like cell line and suggest the importance of the oxidative cytocidal mechanism in this process.